Quality Attributes and Storage of Tomato Fruits as Affected by an Eco-Friendly, Essential Oil-Based Product - Xylia, Panayiota; Ioannou, Irene; Chrysargyris, Antonios; Stavrinides, Menelaos; Tzortzakis, Nikos G. (My University, 2021)
The preservation of fresh produce quality is a major aim in the food industry since consumers demand safe and of high nutritional value products. In recent decades there has been a turn towards the use of eco-friendly, natural products (i.e., essential oils-EOs) in an attempt to reduce chemical-based sanitizing agents (i.e., chlorine and chlorine-based agents). The aim of this study was to evaluate the efficacy of an eco-friendly product (EP-based on rosemary and eucalyptus essential oils) and two different application methods (vapor and dipping) on the quality attributes of tomato fruits throughout storage at 11 °C and 90% relative humidity for 14 days. The results indicated that overall, the EP was able to maintain the quality of tomato fruits. Dipping application was found to affect less the quality attributes of tomato, such as titratable acidity, ripening index and antioxidant activity compared to the vapor application method. Vapor application of 0.4% EP increased fruit's antioxidant activity, whereas tomatoes dipped in EP solution presented decreased damage index (hydrogen peroxide and lipid peroxidation levels), activating enzymes antioxidant capacity (catalases and peroxidases). Moreover, higher EP concentration (up to 0.8%) resulted in a less acceptable product compared to lower concentration (0.4%). Overall, the results from the present study suggest that the investigated EP can be used for the preservation of fresh produce instead of the current commercial sanitizing agent (chlorine); however, the method of application and conditions of application must be further assessed for every commodity tested.
Keywords: Antioxidants; Damage index; Eco-friendly product; Essential oils; Quality preservation; Tomato